When Cryptographers Turn Lead into Gold. - Tsang, P.P.
At its core, a cryptographer's job is to "transmutate" trust: just as alchemists turn lead into gold, cryptographers transmutate trust in one or more assumptions into trust in some other simpler and better-defined assumptions, the ones on which the security of complex monolithic systems rely. Because we can enforce and verify the resulting assumptions' validity more easily, such transmutation makes those systems more secure at a higher assurance. Unlike alchemists, though, cryptographers have successfully constructed some of the building blocks (such as public-key encryption and digital signatures) that play a make-or-break role in many of today's security-critical infrastructures. In this installment of Crypto Corner, we'll look at how cryptographers transmutate trust, identify some of the reasons why they sometimes fail, and investigate how they could do a better job